Implementasi Metode Active Learning dalam Menumbuhkan Kreativitas Berpikir Anak Usia Dini - Mushlih, Ahmad (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
This article discusses a method of active learning in fostering creativity thinking of earlychildhood. The application of active learning methods believed to be expected and canhelp early childhood in creative thinking and find new ideas. The method of activelearning for educators become part of alternative learning to cultivate creativitythinking of early childhood. Therefore, the application of active learning important maycontain learning activities is direct experience, interaction, communication, andreflections need to be run in the process fosters creativity thinking so that earlychildhood is able to find own ideas and new knowledge.